Investigation of GMR Eddy Current Permanent Magnet System for Carbon Steel Corrosion Identification using IoT Unmanned Aerial Vehicles Drone Platform - Ali K.; Joraimee Mohamad A.; Rifai D.; Hazim Aizuddin Othman M.; Mohamed Ayub M.A.; Hussian A.H.; Paw K.S.; Phing C.C.; Yaw C.T.; Ding T.J. (Institute of Physics, 2023)
Aircraft detection; Antennas; Deterioration; Drones; Eddy current testing; Inspection; Internet of things; Pipeline corrosion; Steel corrosion; Accurate testing; Aerial vehicle; Carbon steel corrosion; Change in thickness; Current test; Eddy-current; Leaking pipes; Magnet systems; Measurement of defects; Voltage amplitude; Permanent magnets